Maria Grazia Cianci (a cura di). (2022). Spessori. Il paesaggio come stratificazione. Padova: Il Poligrafo (diségno, 2023)
The book coordinated by professor Cianci is the first volume of a collection of texts on open spaces and their representation, which, although originating in the classes taught at the prestigious Master di II Livello OPEN - Architettura e Rappresentazione del Paesaggio dell’Università degli Studi Roma Tre, which was founded by professor Riccardo Ghio, demonstrates a clear research vocation open to the international scientific community.The quality of the contributions is guaranteed not only by the high scientific level of the authors, who come from different and convergent scientific fields, but also by the experts who make up the scientific committee, whose careers are internationally recognised. [read more]